PENGEMBANGAN MODUL ISLAMIC PARENTING BERBASIS MULTIPLE INTELLIGENCES UNTUK MENGOPTIMALISASI KECERDASAN LINGUISTIK, RUANG-VISUAL, DAN KINESTETIK BADANI ANAK - Fatkhi Fahim; Ragwan Albaar (Universitas Islam Negeri Mataram, 2020)
Good parenting is one of the basic needs of children, therefore parents are obliged to provide appropriate parenting styles for children suitable for the era, so that in the end, parents could form children’s characters with good attitude and intelligence that was honed fully. Based on this, the researcher tried to develop modules that could help parents developing good parenting styles. To answer these problems, researchers used research and development methods. This research produced a product in the form of a module entitled